A New Standard for Crustacean Genomes: The Highly Contiguous, Annotated Genome Assembly of the Clam Shrimp Eulimnadia texana Reveals HOX Gene Order and Identifies the Sex Chromosome - Baldwin-Brown, James G (Genome Biol Evol, 2017)
Vernal pool clam shrimp (Eulimnadia texana) are a promising model system due to their ease of lab culture, short generation time, modest sized genome, a somewhat rare stable androdioecious sex determination system, and a requirement to reproduce via desiccated diapaused eggs. We generated a highly contiguous genome assembly using 46× of PacBio long read data and 216× of Illumina short reads, and annotated using Illumina RNAseq obtained from adult males or hermaphrodites. Of the 120 Mb genome 85% is contained in the largest eight contigs, the smallest of which is 4.6 Mb. The assembly contains 98% of transcripts predicted via RNAseq. This assembly is qualitatively different from scaffolded Illumina assemblies: It is produced from long reads that contain sequence data along their entire length, and is thus gap free. The contiguity of the assembly allows us to order the HOX genes within the genome, identifying two loci that contain HOX gene orthologs, and which approximately maintain the order observed in other arthropods. We identified a partial duplication of the Antennapedia complex adjacent to the few genes homologous to the Bithorax locus. Because the sex chromosome of an androdioecious species is of special interest, we used existing allozyme and microsatellite markers to identify the E. texana sex chromosome, and find that it comprises nearly half of the genome of this species. Linkage patterns indicate that recombination is extremely rare and perhaps absent in hermaphrodites, and as a result the location of the sex determining locus will be difficult to refine using recombination mapping.